Hydrogen sulfide inhibits skeletal muscle ageing by up‐regulating autophagy through promoting deubiquitination of adenosine 5'‐monophosphate (AMP)‐activated protein kinase α1 via ubiquitin specific peptidase 5 - Jia‐He Yang; Jun Gao; Ya‐Qi E; Li‐Jie Jiao; Ren Wu; Qiu‐Yi Yan; Zi‐Yi Wei; Guo‐Liang Yan; Jin‐Long Liang; Hong‐Zhu Li (Wiley, 2024)
Abstract Background Hydrogen sulfide (H2S), the third gasotransmitter discovered, regulates a variety of physiological functions. Whether H2S alleviates skeletal muscle ageing by regulating autophagy has not been reported. Methods Mice were administered 150 mg/kg/day of D‐galactose (D‐gal), and C2C12 myotubes were cultured in 20 g/L D‐gal to induce ageing. Sodium hydrosulfide (NaHS) was employed as an exogenous donor in the treatment group. The intracellular concentration of H2S was quantified by the 7‐azido‐4‐methylcoumarin fluorescence probe. The proteins involved in the ubiquitin‐mediated degradation of AMPKα1 were detected by liquid chromatography tandem mass spectrometry (LC-MS/MS) and co‐immunoprecipitation (Co‐IP). S‐sulfhydration of USP5 was tested by a biotin‐switch assay. Associated proteins were analysed by western blot. Results NaHS was found to effectively restore the H2S content in both ageing gastrocnemius (+91.89%, P < 0.001) and C2C12 myotubes (+27.55%, P < 0.001). In comparison to the D‐gal group, NaHS was observed to increase the mean cross‐sectional area of muscle fibres (+44.91%, P < 0.001), to decrease the collagen volume fraction of gastrocnemius (−81.32%, P = 0.001) and to reduce the β‐galactosidase‐positive area of C2C12 myotubes (−28.74%, P < 0.001). NaHS was also found to reverse the expression of muscle atrophy F box protein (MAFbx), muscle‐specific RING finger protein 1 (MuRF1), Cyclin D1 and p21 in the ageing gastrocnemius tissue (MAFbx: −31.73%, P = 0.008; MuRF1: −32.37%, P = 0.003; Cyclin D1: +45.34%, P = 0.010; p21: −25.53%, P = 0.022) and C2C12 myotubes (MAFbx: −16.38%, P < 0.001; MuRF1: −16.45%, P = 0.003; Cyclin D1: +40.23%, P < 0.001; p21: −35.85%, P = 0.026). The AMPKα1-ULK1 pathway was activated and autophagy was up‐regulated in NaHS‐treated gastrocnemius tissue (p‐AMPKα1: +61.61%, P = 0.018; AMPKα1: +30.64%, P = 0.010; p‐ULK1/ULK1: +85.87%, P = 0.005; p62: −29.07%, P < 0.001; Beclin1: +24.75%, P = 0.007; light chain 3 II/I [LC3 II/I]: +55.78%, P = 0.004) and C2C12 myotubes (p‐AMPKα1: +77.49%, P = 0.018; AMPKα1: +26.18%, P = 0.022; p‐ULK1/ULK1: +38.34%, P = 0.012; p62: −9.02%, P = 0.014; Beclin1: +13.36%, P < 0.001; LC3 II/I: +79.38%, P = 0.017; autophagy flux: +24.88%, P = 0.034) compared with the D‐gal group. The effects of NaHS on autophagy were comparable to those of acadesine and LYN‐1604, and chloroquine could reverse its effects on ageing. LC-MS/MS and Co‐IP experiments demonstrated that USP5 is a deubiquitinating enzyme of AMPKα1. Following the knockdown of USP5, the activation of AMPKα1 was decreased (p‐AMPKα1: −42.10%, P < 0.001; AMPKα1: −43.93%, P < 0.001), autophagy was inhibited (p‐ULK1/ULK1: −27.51, P = 0.001; p62: +36.00, P < 0.001; Beclin1: −22.15%, P < 0.001) and NaHS lost its ability to up‐regulate autophagy. NaHS was observed to restore the expression (gastrocnemius: +62.17%, P < 0.001; C2C12 myotubes: +37.51%, P = 0.003) and S‐sulfhydration (+53.07%, P = 0.009) of USP5 and reduce the ubiquitination of AMPKα1. Conclusions H2S promotes the deubiquitination of AMPKα1 by increasing the expression and S‐sulfhydration of USP5, thereby up‐regulating autophagy and alleviating skeletal muscle ageing.